Challenges of Nation-Branding for Stimulation of Latvian Exports - Bekasova Angelina; Sloka Biruta; Muravska Tatjana (Economics and Business)
The presented research aims to contribute to the conceptualisation of the nation-brand of Latvia with the purpose of stimulation of national export performance. The subject of the research is three aspects presumably challenging the branding of Latvia with reference to national export development. The investigated challenges are the barriers and opportunities for green-branding of Latvia; the absence of the generally accepted indication of the geographical identity of the Baltic region; and the contradictable popular image of Latvia as a cheap country. The research poses two research questions inquiring into the issues of nation-branding of Latvia currently being faced in the context of exports and possible measures to overcome them. The applied research methods are theoretical analysis of scientific literature and empirical analysis of the representation of Latvia on the official website of the Investment and Development Agency of Latvia and its comparison with the official websites of respective institutions in Lithuania and Estonia. The research observes the interconnection between the defined challenges, offers the perspective for the possible transformation of the challenges into nation-branding opportunities, and estimates the green brand of the country as a gateway for feasible solution for the defined challenges and for the stimulation of national exports. In addition, the research identifies further challenges the nation-branding of Latvia is currently facing for further discussion.